Mediasi Credit Risk dalam Hubungan antara Board Independence dengan Financial Distress pada Sektor Perbankan - Sholikhul Ummah; Kosasih Kosasih; Tiar Lina Situngkir (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
This study examines the phenomenon of Financial Distress in the banking industry by considering two main dimensions, namely corporate governance and financial risk. Specifically, this research is designed to test the extent to which Board Independence contributes to Credit Risk, as well as how Credit Risk subsequently affects Financial Distress conditions. The methodology applied employs a quantitative method utilizing secondary data sourced from banking firms registered on the Indonesia Stock Exchange over the period 2020 to 2024. Sample determination was conducted by applying a purposive sampling technique, resulting in 25 companies with a total of 125 observation units. Hypothesis examination was performed through panel data regression analysis. The findings reveal that Board Independence has no significant impact on Credit Risk. In contrast, Credit Risk is demonstrated to exert a positive and statistically meaningful influence on Financial Distress. The implications of these findings suggest that financial pressure experienced by banks is more driven by high credit risk than by the effectiveness of internal corporate governance mechanisms.